Under the Influence: A Sectarian Railway Worker, the Bolsheviks, and the 1905 Russian Revolution - Schibanoff, Susan; Schibanoff, James M. (Journal of Russian American Studies, 2023)
Of Moldovan-Ukrainian heritage, Hariton Czebanov (1886-1962) was administratively exiled with his family to Transcaucasia in 1892 as a religious dissenter (Stundist). Barred from an education, he went to work on the Transcaucasian Railway and joined the Bolshevik Party in protest of his discriminatory treatment. After the 1905 revolution, the party demanded increasingly criminal activity from him; Czebanov took part in robberies and terror attacks (“expropriation”) to fund the party intelligentsia in exile. He was jailed by the tsarist police several times. In 1907, out on bail and facing a sentence of “katorga” (penal servitude), Czebanov could no longer support the “muddy wave” of violence sweeping over the party. He stowed away on a steamer in Poti on the Black Sea and, three months later, arrived at Ellis Island. Once admitted to the U.S., Czebanov wrote a series of three letters detailing his dramatic passage to freedom. The article includes a translation of these detailed letters.